The Influence Of Learning Media And Information Technology-Based Learning On Students' Learning Outcomes In The Citizenship Education Subject In Grade IX - Silalahi, Marintan Florensia; Saragih, Sepriandison; Siahaan, Rina Devi Romauli (CV Putra Publisher, 2025)
This research aims to examine the effect of learning media and information technology-based learning on the learning outcomes of ninth-grade students at UPTD SMP Negeri 4 Pematangsiantar. The study employed a quantitative approach with a quasi-experimental design involving 63 students divided into experimental and control classes. Prior to the intervention, instrument validity tests were conducted with expert validators and a set of 25 valid multiple-choice questions was administered. Data were collected through pre-tests and post-tests. The results show that the control class, taught conventionally, achieved an average pre-test score of 37.88 and a post-test score of 49.25, while the experimental class, which was taught using learning media and technology-based methods, achieved an average pre-test score of 50.37 and a post-test score of 85.16. Hypothesis testing revealed a significant difference, with tcount (3.834) > ttable (0.404) and p-value < 0.05, indicating that the null hypothesis was rejected. The findings demonstrate that the use of learning media and information technology-based learning has a significant positive impact on students’ learning outcomes in Civic Education, enhancing their engagement, critical thinking, and comprehension. This study suggests that integrating digital learning tools can create more effective, interactive, and enjoyable learning experiences